Knowledge Level of Groundnut Farmers in Jaipur District, Rajasthan (Indian Journal of Extension Education, 2011)
Despite of the facts, the groundnut contributes about two-fifth of the total area and production of oilseeds in country. India is facing acute shortage of vegetable oils. This is mainly due to the low productivity of these crops. This may be attributed to a number of factors and constraints, which hinders the adoption of the innovations. These factors and constraints should be identified and remove by developing an effective strategy for farmers.The study was conducted in Govindgarh panchayat samiti of Jaipur district, which was selected purposively. Eight villages namely Ghinoi, Bailabas, Jheera, Samod, Nindola, Khejroli, Hathnoda and Nangal Bharda from four selected gram panchayat were selected with the help of simple random sampling technique. Majority of the groundnut growers had medium knowledge level about the recommended cultivation practices of groundnut. Among the various aspects of different cultivation practices, majority of the farmers had knowledge about ‘Sowing time’, ‘Seed rate’ ‘Irrigation management’, ‘Spacing’, ‘Seed treatment’, ‘Weed management’ and ‘Plant protection measures’.